The Effectiveness of Using Flashcards in Improving Early Childhood Reading Skills - Muhammad Hasanuddin; Abil Alwi Prayoga (CV. Raskha Media Group, 2025)
This study aims to analyze the effectiveness of using flashcards to improve early reading skills in young children. This research is grounded in the need for engaging, interactive learning methods that align with the developmental characteristics of early childhood. The study employed a quasi-experimental design with a pretest–posttest control group. The sample consisted of children aged 4–6 years, divided into an experimental and a control group. The experimental group received reading instruction using flashcards for four weeks, while the control group used conventional teaching methods. The results indicate a significant improvement in children's reading abilities when using flashcards compared to the control group. The improvement is evident in letter recognition, syllable understanding, and the ability to read simple words. A t-test supports the finding that flashcards have a positive, significant impact on the development of early reading skills. Therefore, it can be concluded that flashcards are an effective and practical learning medium that supports early literacy development in young children.